War is not our Profession – Paradoxes for a Moralization and Morality of War - Pili, Giangiuseppe (Filosofia Morale/Moral Philosophy, 2022)
War is the evil trivialized, and peace is the contextual precondition for ordinary morality. The essence of war is a suspension of morals, whatever the parties one wants to consider. However, not all sides in war hold equal responsibility in establishing the conditions for suspending ordinary morality. It is possible to ground accountability and responsibility of war and warfare on the ground of a compatibilist neo-Kantian morality. The account holds that war is the ultimate absence of morals, where only evil is possible, and, at the same time, the blame is one-sided. Ultimately, peace is a common good which is where proper moral actions are possible.